Representations of women in Suchen Christine Lim's fistful of colours and a bit of earth - Shahrul Annuar bin Othman (Kulliyyah of Islamic Revealed Knowled and Human Sciences, International Islamic University Malaysia, 2009)
This research attempts to compare and critically analyse two selected novels by Suchen Christine Lim from a feminist literary point of view. The feminist literary criticism would specifically be drawn upon from a Third World feminist perspective. Particularly focusing on Fistful of Colours (1993) and A Bit of Earth (2001), this research critically analyses the representations of women in the two novels. The women in the two novels experience various social circumstances. Their subordination and oppressed situations were greatly affected by patriarchy and other factors. These factors range from the women’s social castes and classes to their personal values and beliefs.